THE MODERNIZATION PROCESSES IN THE MATERIAL CULTURE OF THE PEOPLES OF DAGESTAN IN THE LATEST TIME: TRADITIONS AND INNOVATIONS - R. I. Seferbekov (Современная наука и инновации)
The article considers the influence of modernization processes that have unfolded in Russia in modern times on the material culture of the peoples of Dagestan. The degree of preservation of traditional elements and introduction of innovations in settlement culture, dwellings, clothes and food of Dagestanis is investigated. As the author believes, the revolutionary and evolutionary processes that have taken place in society in recent decades have directly or indirectly affected the elements of material culture, partially or completely altering them.